Sistem Arsitektur Manajemen Bangunan untuk Memaksimalkan Swakonsumsi pada Bangunan Universitas: Studi Kasus - Puspita, Yumna; Nanda, Rezky Mahesa; Arif M. Natawidjaja, Reyza; Friansa, Koko; Pradipta, Justin; Armanto Mangkuto, Rizki; N. Haq, Irsyad; Leksono, Edi; Wasesa, Meditya (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2023)
Due to its intermittent nature, significant adoption of solar PV into the grid can decrease grid reliability. One solution to increase it is to increase PV self-consumption with two methods: adding Energy Storage System (ESS) and conducting Demand Side Management (DSM). University building has a distinct characteristic in its complex dynamics. Therefore, there is a lack of research to control both methods of increasing self-consumption. This paper aimed to do an integrated literature review on increasing self-consumption and then propose a system architecture recommendation for university building management based on the review. The Smart Grid Architectural Model (SGAM) evaluated the case study object. The result showed that a data-driven controller has been chosen as the most suitable controller for the university building management system. The data needed to build a data-driven controller could be obtained through readily available sensors in the case study object, making it feasible for implementation.